2017
DOI: 10.1186/s12885-017-3291-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30a regulates cell proliferation and tumor growth of colorectal cancer by targeting CD73

Abstract: BackgroundMicroRNAs are non-coding RNAs which regulate a variety of cellular functions in the development of tumors. Among the numerous microRNAs, microRNA-30a (miR-30a) is thought to play an important role in the processes of various human tumors. In this study, we aimed to explore the role of miR-30a in the process of colorectal cancer (CRC).MethodsThe quantitative real-time PCR and western blot analysis were used to detect the expressions of miR-30a and CD73 in CRC cell lines and clinical tissues. The lucif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Bioinformatic analysis has predicted that miRNAs may regulate over 30% of protein-coding genes (12); therefore, miRNAs play key roles in a large number of physiological and pathological processes, such as cell proliferation, cycle, apoptosis, metabolism, differentiation, motility, epithelialmesenchymal transition and metastasis (13)(14)(15)). An increasing body of evidence indicates that aberrantly expressed miRNAs are observed in almost all types of human cancer, such as CRC (16), gastric carcinoma (17), lung cancer (18) and cervical carcinoma (19). Certain miRNAs may act as oncogenes or tumour-suppressor genes which primarily depends on the roles of their target genes (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis has predicted that miRNAs may regulate over 30% of protein-coding genes (12); therefore, miRNAs play key roles in a large number of physiological and pathological processes, such as cell proliferation, cycle, apoptosis, metabolism, differentiation, motility, epithelialmesenchymal transition and metastasis (13)(14)(15)). An increasing body of evidence indicates that aberrantly expressed miRNAs are observed in almost all types of human cancer, such as CRC (16), gastric carcinoma (17), lung cancer (18) and cervical carcinoma (19). Certain miRNAs may act as oncogenes or tumour-suppressor genes which primarily depends on the roles of their target genes (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed miRNA was responsible for the dysregulation of CD73 expression [30, 31]. We further investigated the potential upstream miRNA of CD73 in HCC.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, miR-30a was found to target NT5E in CRC ( 64 ). In this study, transfection with miR-30a reduced NT5E expression on the mRNA and on protein level and direct interaction of miR-30a with the NT5E 3′-UTR was demonstrated via luciferase reporter assays.…”
Section: Micrornas (Mirnas) Regulating Nt5e Expressionmentioning
confidence: 99%